Pengambilan Langkah Perbaikan sebagai Bagian dari Evaluasi Strategi Pelayanan Penanaman Modal dalam Peningkatan Kualitas PTSP - Permatasari, Rochvika Ariesta (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2022)
Due to minimize obstacles and maximize the preparation and implementation of investment strategies, Pasuruan Regency Government needs to implement strategic management, especially in strategy evaluation. Taking corrective action to improve the strategy in a series of activities to evaluate the investment service strategy are an important step to make some continuous improvement in the investment service strategy. The purpose of this study was to examine the process at the stage of taking corrective action in evaluating strategies at the Office of Investment and Integrated Services (DPMPT) of Pasuruan Regency. This research uses a case study method with a qualitative approach. The results shows that in the process of taking corrective action, have been met the criteria of consistency, but have not met the suitability, eligibility and benefit criteria, because strategists did not consider the quantity and quality of the resources within the process of corrective action moreover the strategists did not take some corrective action in the case of previous formulated program was not implemented successfully.